Significance of routine digital rectal examination in adults presenting with abdominal pain. - Manimaran, N. (2004)
AIM: Routine digital rectal examination (DRE) in children with abdominal pain has slowly gone out of practice but is still performed routinely in adults. This study was undertaken to assess the significance of routine DRE in adults with acute abdominal pain. PATIENTS AND METHODS: A total of 100 consecutive adults admitted to the emergency surgical unit with acute abdominal pain were studied prospectively. Following DRE, patients who were willing to participate in the study were requested to complete an anonymous questionnaire. The house officer conducted the rectal examination at admission and also completed an evaluation sheet. RESULTS: A working diagnosis of acute appendicitis in 38 patients and gastroduodenal, pancreatobiliary pathology in 24 patients was made. DRE did not alter clinical diagnosis or initial management in any of the 100 patients. Routine DRE did not detect any unrelated pathology. Of the patients, 93 wanted to know why rectal examination was required. Overall, 78 patients rated the DRE as uncomfortable. Although 43 were willing for DRE as a routine, 54 patients preferred to have the DRE at the time of other bowel tests rather than at the time of the emergency admission. CONCLUSIONS: Various routine medical procedures have given way to evidence-based practice. This study has demonstrated the limited role of routine DRE in adults with no anorectal or GI symptoms during their initial evaluation for acute abdominal pain.